Effects of chitosan on ruminal fermentation, nutrient digestibility, and milk yield and composition of dairy cows - Gomes De Paiva, Pablo [UNESP]; Ferreira De Jesus, Elmeson [UNESP]; Del Valle, Tiago Antonio; Ferreira De Almeida, Gustavo; Costa, Artur Gabriel Brao Vilas Boas; Consentini, Carlos Eduardo Cardoso; Zanferari, Filipe; Takiya, Caio Seiti; Bueno, Ives Cláudio Da Silva; Rennó, Francisco Palma (CSIRO Publishing, 2017)
Our objective was to evaluate the effects of providing increasing levels of chitosan on nutrient digestibility, ruminal fermentation, blood parameters, nitrogen utilisation, microbial protein synthesis, and milk yield and composition of lactating dairy cows. Eight rumen-fistulated Holstein cows [average days in lactation ≤ 215 ± 60.9; and average bodyweight (BW) ≤ 641 ± 41.1 kg] were assigned into a replicated 4 × 4 Latin square design, with 21-day evaluation periods. Cows were assigned to be provided with four levels of chitosan, placed into the rumen through the fistula, as follows: (1) Control: with no provision of chitosan; (2) 75 mg/kg BW; (3) 150 mg/kg BW; and (4) 225 mg/kg BW. Chitosan had no effect on dry matter intake (P > 0.73); however, chitosan increased (P ≤ 0.05) crude protein digestibility. Propionate concentration was increased (P ≤ 0.02), and butyrate, isobutyrate, isovalerate and acetate:propionate ratio were decreased (P ≤ 0.04) by chitosan. Chitosan had no effect (P > 0.25) on acetate, pH and NH3 ruminal concentration. Glucose, urea, and hepatic enzyme concentrations in the blood were similar (P > 0.30) among treatments. Nitrogen balance was not affected, but chitosan increased milk nitrogen (P ≤ 0.02). Microbial protein synthesis was not affected by chitosan (P > 0.44). Chitosan increased (P ≤ 0.02) milk yield, fat-corrected milk, protein and lactose production. Chitosan changes ruminal fermentation and improves milk yield of lactating dairy cows; therefore, we conclude that chitosan can be used as a rumen modulator instead of ionophores in diets for dairy cows.
Keywords: additive; antimicrobial; dry matter intake.